Non-Coding RNAs in Pediatric Solid Tumors - Smith, Christopher M.; Catchpoole, Daniel; Hutvagner, Gyorgy (Frontiers in Genetics, 2019)
Pediatric solid tumors are a group of extracranial solid tumors representing approximately 40% of childhood cancers. Pediatric solid tumors are believed to arise as a result of disruptions in the developmental process of precursor cells which lead them to accumulate cancerous phenotypes. In contrast to many adult tumors, pediatric tumors typically feature a low number of genetic mutations in protein-coding genes which could explain the emergence of these phenotypes. It is likely that oncogenesis occurs after a failure at many different levels of regulation. ncRNAs comprise a group of functional RNA molecules that lack protein coding potential but are essential in the regulation and maintenance of many epigenetic and post-translational mechanisms. This group includes the small RNAs such as miRNAs, siRNAs, piRNAs, snoRNAs and snRNAs, as well as long ncRNAs which until recently were believed to lack functional relevance. Indeed, research has accumulated a large body of evidence implicating many non-coding RNAs (ncRNAs) in the regulation of well-established oncogenic networks in pediatric solid tumors. Our current progress of the mechanisms of key ncRNAs in the context of pediatric solid tumors are discussed in this review, as well as a brief discussion of possible future directions.